Reassessing the Pediatric Dosing Recommendations for Unfractionated Heparin Using Real‐World Data: A Pharmacokinetic–Pharmacodynamic Modeling Approach. (12th January 2022) - Salem, Ahmed M.; Niu, Tao; Li, Chao; Moffett, Brady S.; Ivaturi, Vijay; Gopalakrishnan, Mathangi
Abstract: Optimal pediatric dosing of unfractionated heparin (UFH) is challenging because of the paucity of clinical outcome and pharmacokinetic–pharmacodynamic (PK/PD) studies in pediatrics. This study aimed to: (i) develop a PK/PD model for UFH, quantified by anti‐factor Xa assay, and the UFH effect, measured by activated partial thromboplastin time (aPTT); and (ii) use simulations to evaluate pediatric UFH infusions for achieving the anti‐factor Xa (0.3–0.7 IU/mL) therapeutic target. Electronic health record data were retrospectively collected from 633 patients aged <19 years admitted to Texas Children's Hospital. The PK/PD model was developed using a 70% (training)/30% (testing) split‐sample approach. A 1‐compartment PK model with linear elimination adequately described the UFH PK. An allometrically scaled body weight on clearance (CL) and volume of distribution (Vd) with an age‐dependent maturation function of extracellular water on Vd were the covariates identified. Comparable with literature, the typical values for CL and Vd were 3.28 L/(h·50 kg) and 8.83 L/50 kg, respectively. A linear model adequately described the UFH–aPTT relationship with an estimated slope of 150 seconds/(IU/mL). Simulations of the currently recommended starting infusions (28 IU/h/kg for pediatrics <1 year old or 20 IU/h/kg for pediatrics >1 year old) showed that the anti‐factor Xa therapeutic target was achieved only in 15.3%, 14.6%, 36.9%, and 45.11% of subjects in the age groups of <1 year, 1–6 years, 6–12 years, and 12–19 years, respectively. In conclusion, the UFH anti‐factor Xa target is not achieved initially, especially in young pediatrics, suggesting the need to optimize UFH dosing to achieve higher therapeutic success.